Research progress in reinforcing system of hydrogenated nitrile rubber - "HUANG Xiu-xu1 a, LI Shi-kun1 b, DU Zheng-peng1 a, CAI Rong-qiang1 b, WANG Feng-ling1 b, ZHENG Fang-yuan2, LI Zai-feng1 b" (Hecheng xiangjiao gongye)
"The research status of reinforcing fillers, such as carbon black, biomass silicon carbon, carbon nanotubes, graphene, silica, silicate and ionic polymer for the composite modification of hydrogenated nitrile rubber was systematically reviewed with 53 references, and the reinforcing characteristics of different types of reinforcing fillers for hydrogenated nitrile rubber were introduced in detail. Finally, the development direction of new reinforced fillers was prospected. "